Modeling of continuous dynamic recrystallization of Al-Zn-Cu-Mg alloy during hot deformation based on the internal-state-variable (ISV) method. (July 2018) - Sun, Z.C.; Wu, H.L.; Cao, J.; Yin, Z.K.
Abstract: Al-Zn-Cu-Mg alloys (e.g., AA7075) have been widely used to form structural components in aerospace and other industries. For Al-Zn-Cu-Mg alloys, although dynamic recovery was dominant in hot deformation, dynamic recrystallization also occurred frequently, such as continuous dynamic recrystallization (CDRX), for which various mechanisms were found, e.g. subgrain boundary migration, subgrain coalescence, and subgrain rotation. However for the as-extruded AA7075 alloy subjected to hot compression, the mechanisms of CDRX process and model for it are lacking. In this paper by conducting thermal simulation compression tests combined with electron back scattered diffraction (EBSD) experiments, a continuous dynamic recrystallization (CDRX) process during the hot deformation of the as-extruded Al-Zn-Cu-Mg alloy (AA7075) is revealed based on the analysis on deformation behavior and characteristics of the recrystallized microstructures. It was found that subgrains, which were formed through dynamic recovery (DRV), rotated by absorbing dislocations into its boundaries, and resulted in the formation of the recrystallized grains. Then based on the explored CDRX mechanism, the dislocation density, subgrain boundary area, recrystallized grain boundary area, high angle grain boundary area and subgrain boundary misorientation were determined as internal-state-variables, and a continuous dynamic recrystallization model for AA7075 alloy was developed. In the established model, the process of subgrain rotation was described by introducing subgrain boundary stored energy, which related to dislocation density, subgrain size and misorientation. Finally, the continuous dynamic recrystallization model was combined with a constitutive model for the unified prediction of the flow stress and the microstructure evolution during the hot deformation of AA7075. Predictions of the model are in good agreement with the experimental ones. Highlights: CDRX occurred during hot compression of as-extruded Al-Zn-Cu-Mg alloy (AA7075). Subgrain formed in DRV and rotated by absorbing dislocations to result in HABs and CDRX. CDRX was modeled based on ISV and combined with constitutive model for unified prediction. Subgrain rotation was modeled by introducing subgrain stored energy.